The Effects of High-Fidelity Simulation on Salivary Cortisol Levels in SRNA Students: A Pilot Study - Terri Jones; Sarah Goss; Bethany Weeks; Hiroko Miura; Damian Bassandeh; Dennis Cheek (The Scientific World Journal)
The use of clinical simulation in graduate level nursing education provides the opportunity for students to learn and apply theoretical practices of nursing care in a safe and controlled environment. It was postulated that laboratory simulation would mimic the stress levels of a real clinical situation as measured by the stress hormone cortisol. The purpose of this study was to determine whether high-fidelity simulation approximates the stress experienced by nurse anesthesia students in the operating room. Participants (n = 21) were recruited from an accredited nurse anesthesia program in the southern U.S. Saliva was collected for 3 days under controlled conditions for baseline data. Next, saliva was collected for 3 days: the day before, the day of, and the day after simulation. The same process was repeated for the first clinical day in the operating room. The participants acted as their own control. There was a significant (p < 0.05) increase in cortisol levels during laboratory simulation as compared to baseline values. Although levels of cortisol were higher during clinical time than baseline, this increase was not significant (p > 0.05), and levels were lower than levels during simulation. Laboratory simulation of patient scenarios raised the stress hormone cortisol level threefold above baseline levels in nurse anesthesia students, while actual clinical experience did not.